2014
DOI: 10.1093/heapol/czu118
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: knowledge and practice of providers treating uncomplicated malaria at public and mission health facilities, pharmacies and drug stores in Cameroon and Nigeria

Abstract: Background Artemisinin combination therapy (ACT) has been the first-line treatment for uncomplicated malaria in Cameroon since 2004 and Nigeria since 2005, though many febrile patients receive less effective antimalarials. Patients often rely on providers to select treatment, and interventions are needed to improve providers’ practice and encourage them to adhere to clinical guidelines.Methods Providers’ adherence to malaria treatment guidelines was examined using data collected in Cameroon and Nigeria at publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Information on pre-existing antimalarial preferences was gathered from baseline and preintervention surveys, 32 49 interview transcripts Tanz1 and unpublished reports, 54 although no data were available for five studies Afgh1,Ghan1,Tanz3,Uga1,Uga2 . The data suggest an association between the use of ACTs for positive mRDTs and baseline preferences for, or use of, ACTs rather than other antimalarials.…”
Section: Resultsmentioning
confidence: 99%
“…Information on pre-existing antimalarial preferences was gathered from baseline and preintervention surveys, 32 49 interview transcripts Tanz1 and unpublished reports, 54 although no data were available for five studies Afgh1,Ghan1,Tanz3,Uga1,Uga2 . The data suggest an association between the use of ACTs for positive mRDTs and baseline preferences for, or use of, ACTs rather than other antimalarials.…”
Section: Resultsmentioning
confidence: 99%
“…Hence there is still the need for the PPMVs to be trained periodically on the recommended guideline for diagnosis and treatment of uncomplicated malaria. There was a report on PPMVs having poor access to the recommended treatment guideline as similarly documented in a study conducted by Mangham-Jefferies et al [28] among drug stores owners in Nigeria and Cameroon but at variance with findings of Adibe et al in a study conducted among PPMVs in Enugu State, Nigeria which reported 75.6% had access to the recommended treatment guideline [17].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing provider knowledge may be a first step towards ensuring the delivery of first-line treatments. That said, some studies have found no evidence of a relationship between providers’ knowledge and practice, and have suggested that provider preference is a stronger predictor of appropriate case management practices [ 40 ]. As such, simply increasing knowledge of the first-line treatment may have a limited effect, as supported by other studies [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%